2022
DOI: 10.3390/ijms232314983
|View full text |Cite
|
Sign up to set email alerts
|

The Patatin–Like Phospholipase Domain Containing Protein 7 Regulates Macrophage Classical Activation through SIRT1/NF-κB and p38 MAPK Pathways

Abstract: Lysophosphatidylcholine (LPC) is a bioactive lipid that modulates macrophage polarization during immune responses, inflammation, and tissue remodeling. Patatin-like phospholipase domain containing protein 7 (PNPLA7) is a lysophospholipase with a preference for LPC. However, the role of PNPLA7 in macrophage polarization as an LPC hydrolase has not been explored. In the current study, we found that PNPLA7 is highly expressed in naïve macrophages and downregulated upon lipopolysaccharide (LPS)-induced polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To further explore whether Sirt1 regulated macrophage polarization through the MAPK signaling pathway and oxidative stress response, we detected the levels of key proteins in the MAPK signaling cascade (P38, JNK, NF-κB p65, AP-1) and antioxidant stress response (Nrf2 and HO-1) by activating or inhibiting Sirt1 levels in THP-1 cells. Zhao et al [ 25 ] conducted a study on the effect of Patatin-like phospholipase domain-containing protein 7 (PNPLA7) on macrophage polarization. The study found that overexpression of PNPLA7 increased Sirt1 levels and repressed p-P38 MAPK levels, thereby suppressing proinflammatory characteristics during LPS-induced M1 polarization, while knockdown of PNPLA7 yielded the opposite results.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore whether Sirt1 regulated macrophage polarization through the MAPK signaling pathway and oxidative stress response, we detected the levels of key proteins in the MAPK signaling cascade (P38, JNK, NF-κB p65, AP-1) and antioxidant stress response (Nrf2 and HO-1) by activating or inhibiting Sirt1 levels in THP-1 cells. Zhao et al [ 25 ] conducted a study on the effect of Patatin-like phospholipase domain-containing protein 7 (PNPLA7) on macrophage polarization. The study found that overexpression of PNPLA7 increased Sirt1 levels and repressed p-P38 MAPK levels, thereby suppressing proinflammatory characteristics during LPS-induced M1 polarization, while knockdown of PNPLA7 yielded the opposite results.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the role of PNPLA7 in choline/methionine metabolism, which is rather liver-specific, the broad distribution of PNPLA7 in many tissues that do not express BHMT implies that this lysophospholipase may also participate in other choline-related processes, which include not only recycling of choline into membrane PC through the Kennedy pathway, but also biosynthesis of sphingomyelin, generation of the neurotransmitter acetylcholine, activation of the sigma receptor that enhances Ca 2+ signaling, and supply of GPC as an osmolyte, among others. A recent study has shown that PNPLA7 is abundantly expressed in macrophages and prevents their M1 polarization, possibly through sequestering pro-inflammatory LPC signaling [ 78 ]. It is also important to clarify the functional segregation or redundancy of the two related enzymes PNPLA6 and PNPLA7 in tissue-specific contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why there was no effect on IL6 expression or action in our experiments. However, the expression of Pnpla7 in cultured murine macrophages was reduced by bacterial lipopolysaccharide ( 48 ). Moreover, overexpression of Pnpla7 suppressed and gene silencing of Pnpla7 enhanced lipopolysaccharide-induced expression of proinflammatory cytokines, such as IL-1β (gene Il1b ) ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of Pnpla7 in cultured murine macrophages was reduced by bacterial lipopolysaccharide ( 48 ). Moreover, overexpression of Pnpla7 suppressed and gene silencing of Pnpla7 enhanced lipopolysaccharide-induced expression of proinflammatory cytokines, such as IL-1β (gene Il1b ) ( 48 ). While these results suggest a direct role for PNPLA7 in regulation of cytokine secretion from murine macrophages, it would not be unreasonable to suggest that secretion of IL-6 from human skeletal muscle cells is regulated in a different manner.…”
Section: Discussionmentioning
confidence: 99%